The Design of Infant Warmer with Simple Blue Light Therapy LED Addition - Fatahah Dwi Ridhani; Nur Hasanah Ahniar; Ansor Ibrahim Usman; Moch. Prastawa Assalim Tetra Putra; Suharyati Atmadja (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
This paper presents a result of experiment on adding built-in blue light therapy on a purpose built infant warmer. Blue light therapy are often used in case of jaundice and usually a separated unit with added complexity. The blue light assembly was LED based that placed along the heater bar, placed on its aluminum strips and spaced to prevent being affected by the heater. Blue light LED specification was an SMD 5730 dimension with 465nm wavelength driven at 160mA at 12V for the three clusters of LED. Measured light output was around 618-716 lux and measured at the bed area with good uniformity for area under the heater bar at around 60-69 lux. There was another bottom blue LED source but the effect was negligible. The system uses a 10A maximum current source of 12V power supply exclusively for the LED arrangement and another 3A maximum current source of 5V power supply for supplying the rest of the control systems. The LED was controlled by a switch button and monitored for its activation by means of measuring the voltage difference with resistor circuits through the button switch. It works as intended.